2010
DOI: 10.1159/000288236
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Trial of the Effects of Hydrochlorothiazide on Nocturnal Enuresis

Abstract: Objective: To assess the efficacy, tolerability and side effects of the diuretic hydrochlorothiazide (HCTZ) in the management of monosymptomatic nocturnal enuresis by a placebo-controlled double-blind crossover trial. Patients and Methods: Forty patients suffering from nocturnal enuresis were blindly randomized into 2 groups of equal numbers. Group 1 first received placebo for 3 months, and group 2 received oral HCTZ once daily for the same period. Both groups, after a 2-week wash-out period, were crossed over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Based on our findings, children who became normocalciuric after receiving HCT had significant PMNE clinical response. The findings of Alawwa et al ( 17 ) and mechanisms explained by Park et al ( 14 ) about the relationship between IHC and NE confirm our results. Due to the low cost, availability, ease of use and minor complications of HCT ( 13 ), it can be an effective drug in the treatment of PMNE in children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on our findings, children who became normocalciuric after receiving HCT had significant PMNE clinical response. The findings of Alawwa et al ( 17 ) and mechanisms explained by Park et al ( 14 ) about the relationship between IHC and NE confirm our results. Due to the low cost, availability, ease of use and minor complications of HCT ( 13 ), it can be an effective drug in the treatment of PMNE in children.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the improvement of PMNE in children receiving conservative treatment with HCT was more significant than the group receiving conservative treatment alone. Therapeutic efficacy of HCT on NE has been studied in only one study in 2010, by Alawwa et al ( 17 ). In this study, 1 mg/kg/day oral HCT and placebo were used for treatment of 40 patients with NE and clinical responses of the patients were studied for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted on 40 children with NE and they used placebo and 1 mg/kg/day oral HCT; clinical responses of children were studied during a period of 3 months. It was observed that HCT reduced episodes of wet night better than placebo, but both of them were statistically effective on reducing the mean of wet nights; the current study also came to the same conclusion (21). Yousefichaijan et al in a study on the therapeutic effect of HCT on PMNE only in males, compared the case (HCT and conservative treatment) and control (conservative treatment) groups.…”
Section: Discussionsupporting
confidence: 79%
“…We read with great interest the recent contribution by AlAwwa et al [1] . They showed the beneficial effect of hydrochlorothiazide (HCTZ) on nocturnal enuresis (NE), but did not suggest the possible mechanisms.…”
Section: Dear Sirmentioning
confidence: 93%